A randomized phase 3 study of maintenance therapy with S‐1 plus best supportive care versus best supportive care after induction therapy with carboplatin plus S‐1 for advanced or relapsed squamous cell carcinoma of the lung (WJOG7512L). Issue 16 (2nd June 2020) - Tanaka, Kaoru; Morita, Satoshi; Ando, Masahiko; Yokoyama, Takuma; Nakamura, Atsushi; Yoshioka, Hiroshige; Ishiguro, Takashi; Miura, Satoru; Toyozawa, Ryo; Oguri, Tetsuya; Daga, Haruko; Ko, Ryo; et al.
Abstract : Background: A randomized phase 3 study was performed to investigate the efficacy and safety of maintenance therapy with S‐1 after induction therapy with carboplatin plus S‐1 in patients with advanced squamous non–small cell lung cancer (NSCLC). Methods: Chemotherapy‐naive patients with advanced or relapsed squamous NSCLC were treated with carboplatin (area under the curve of 5 on day 1 every 3 weeks) plus S‐1 (40 mg/m 2 twice per day on days 1‐14 every 3 weeks) as induction therapy. Patients who did not progress after 4 cycles of induction therapy were randomized to receive either S‐1 plus best supportive care (BSC) or BSC alone. The primary objective of the study was to confirm the superiority of S‐1 plus BSC in comparison with BSC alone with respect to progression‐free survival. Results: Of the 365 patients enrolled in the study, 347 participated in the induction phase, and 131 of these individuals were randomized to receive S‐1 plus BSC (n = 67) or BSC alone (n = 64). The risk of disease progression was significantly lower for patients in the S‐1 plus BSC arm than those in the BSC‐alone arm (hazard ratio, 0.548; 95% confidence interval, 0.374‐0.802; P  = .0019). The most common toxicities during maintenance therapy with S‐1 included anorexia, anemia, and fatigue, but most cases were not severe. Conclusions: Continued maintenance with S‐1 plus BSC is an effective and well‐tolerated treatment option for patients with advanced squamous NSCLC previously treated with carboplatin plus S‐1. Abstract : The West Japan Oncology Group 7512L study compares S‐1 maintenance therapy with best supportive care alone in patients with advanced squamous non–small cell lung cancer after induction therapy with carboplatin plus S‐1. The primary endpoint of the study has been met with the detection of a significant improvement in progression‐free survival with S‐1 maintenance therapy.